Perancangan Aplikasi Mobile Location Based Service (LBS) Untuk Lokasi Penyewaan Rumah Kos di Kota Semarang Berbasis Android - Maulana Muhammad Iqbal; R. Rizal Isnanto; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Until now, Diponegoro University has become one of the favorite State Univesity for Senior High school students to continuing education college. During this time existing information of boarding house around the Diponegoro University still conventional, there is no mobile device applications that provide information and location of boarding house. Based on this information, it should be made an application on android Operating System to search the location of the boarding house in Semarang. Design of Mobile Location Based Service Application for boarding house locations in Semarang Based Android, a client server application created by using the Java, PHP, jQuery and MySQL for database. Intake form of latitude and longitude coordinates utilize the GPS feature on the mobile device and will be shown on Google Maps APIs. The results of this application design is the realization of a application that can search the location of boarding house based on android operating system, with features that can help users find the position of the boarding house. The application can help boarding house owners to promote their boarding house information rooming in their possession to the user. The design also introduces application android application development using the Global Positioning System functions for user navigation.